Marriage guardian examination in banjar district: A situational approach and regulatory discretion - Fauziyah Hayati (Institute Of computer Science (IOCS), 2024)
This research explores the practices of examining the completeness of marriage guardian requirements at the Religious Affairs Office (KUA) in Banjar Regency. Despite the examination being carried out in accordance with the existing regulations, it is undeniable that there are challenges in the field, leading to occasional adjustments in the examination process based on the prevailing situations and conditions. The objective of this study is to uncover the reasons behind these practices based on the Minister of Religious Affairs Regulation No. 20 of 2019.This research employs an empirical legal study with a qualitative descriptive approach. The aims are: (1) To understand the practices of examining marriage guardians at the KUA in Banjar Regency, and (2) To identify the reasons underlying the variations in the examination of marriage guardians at the KUA in Banjar Regency. The analysis reveals that at the KUA in Banjar Regency (including Beruntung Raya Sub-District, Gambut Sub-District, and Kertak Hanyar Sub-District), examinations of marriage guardians are conducted in accordance with the applicable regulations but still occur on a situational basis. Recognition from the marriage guardian is not solely verbal but also aligns with the valid documents in Indonesia. Prudence is highly emphasized in these examinations, although some are based on the principle of trust alone.